Performance of glucoamylase self‐producing eBOOST™ GT yeast on ethanol production. Issue 6 (13th July 2021) - Viswanathan, Mothi Bharath; Bhatia, Gitanshu; Jansen, Mickel; Basu, Rahul; Singh, Vijay
Abstract: Background and objectives: This study demonstrates ethanol production using a new yeast strain called eBOOST™ GT, that can self‐produce glucoamylase and reduce glycerol production. The advanced yeast's potential with added glucoamylase expression was investigated by observing and comparing its final ethanol and glycerol concentration against granular starch hydrolyzing enzyme (GSHE) catalyzed Ethanol Red fermentation. Findings: The ethanol concentration in advanced yeast fermentation with self‐produced glucoamylase was measured at 10.03% v/v, which is 40% less than GSHE catalyzed Ethanol Red fermentation. However, upon externally providing additional glucoamylase (at 50% of the recommended dosage), eBOOST™ GT was able to produce similar ethanol concentration, compared to Ethanol Red fermentation catalyzed with GSHE enzyme. Furthermore, in this scenario, the glycerol concentration at the end of fermentation was 31% less than observed concentrations in operating with only self‐produced glucoamylase and 72% less than conventional GSHE fermentation. Conclusions: The newly engineered yeast strain proves its capability to meet GSHE catalyzed ethanol yield at reduced enzyme consumption, and therefore, reduction in enzyme costs. The rate of substrate consumption and process economics are areas of future research for eBOOST™ GT ethanol fermentation. Significance and novelty: This study provides important information on enzyme reduction and ethanol production, while using a self‐enzyme producing yeast.